Investigation of the Association of Interpersonal Skills of Exercise Teachers on the Mental Health, Competitive Trait Anxiety, and Perception of Athlete Students' Success - Houriyhe Dehghanpouri; Elham Vosadi; Mansoureh Mokaberian (Shiraz University of Medical Sciences, 2021)
Background: As the team leader, a coach is a strong creator, who paves the way for the athletes' progress and provides a large portion of the required conditions for the victory and success. The present study aimed to investigate the association between interpersonal skills of exercise teachers and the mental health, competitive trait anxiety, and perception of the athlete students' success in the 30th round of sports competitions of female students across Iran. Method: The current research was a cross-sectional study. It was conducted from August 11, 2019 to August 16, 2019. The statistical population of the study consisted of all the athlete students participating in the 30th sports competition round of female students from all over Iran (700 people). The age of the participants ranged from 12 to 17 years (14.25±1.72). The questionnaires were distributed in a community of all student-athletes among 300 students via purposeful and accessible method. Finally, out of the distributed questionnaires, 264 questionnaires were collected during the research. The data were collected through a questionnaire. Data analysis was also performed utilizing SPSS and AMOS software. The data obtained through the questionnaires were analyzed using Pearson's correlation test based on the structural equation modeling. Results: The results indicated a significant positive relationship between mental health of the athlete students and interpersonal skills of exercise teachers (r=0.235, P=0.001), perception of the athlete students' success and interpersonal skills of the exercise teachers (r=0.280, P=0.001), perception of success and students' mental health (r=0.146, P=0.005), and perception of the athlete students' success and their competitive trait anxiety (r=0.193, P=0.002). Furthermore, there was a significant negative relationship between competitive trait anxiety of the athlete students and interpersonal skills (r=-0.322, p <0.001) and their competitive trait anxiety and their mental health (r=-0.296, P=0.001). The model indices also showed a good fit. The P (ჯ2) was equal to 0.313 and the RMSEA was estimated to be lower than 0.1 (0.07). The other model fit indices, such as the TLI, NFI, CFI, IFI, RFI, and CMIN/DF, with estimated values of 0.92, 0.951, 0.94, 0.94, 0.911, and 1.45, respectively, all indicated the goodness of fit and confirmed the research model. Conclusion: According to the research findings, it could be suggested to provide further essential communication and coaching training for exercise teachers to have more influence and control over athlete students while providing tactical and technical guidance during the competition and training.